Socio-Political Consequences of Russian Influence on the Northern Lands of Iran (Mid 19th and 20th Centuries) - Seyed Abbas ali Razavi Piranshahi (توسعه اجتماعی)
Following the expansion of industry and trade in Europe and its spread and intensification in the East, Russia did not want to keep up with this trend too. Although Russia's trade relationship with Iran dates back to the Safaviye, however, with regard to the open water project (Persian Gulf), which was on the Russian agenda since "Great Peter", from the Qajar period, during the Golestan, Turkmen-Chay and Akhal treaties, it was able to separate areas from Iran! These lands separated from Iran became one of the main colonies in Russia! But the influence of Russia in Iran is not limited to these areas, and with all its might, it began to exert economic, political and social influence in other northern regions of Iran! As Gilan turned into the economic, political and social gates of Iran with Russia and, consequently, Europe. This issue has had positive outcomes beyond negative implications. The migration of Iranian nationals to Russia and vice versa, the spread of libertarian ideas in Iran, the spread of alienation between Iranians (the forest movement) and the fact that Iran's revolutionaries provided their weapons from Russia, especially the Caucasus. Modern thought, the establishment of new schools and literacy even among girls, tobacco movements, constitutionalism and etc, were consequences of this relationship.